Breaking Through Liminal Spaces: A Study of Adrienne Kennedy’s Funnyhouse of a Negro - Németh, Lenke (FOCUS: Papers in English Literary and Cultural Studies, 2024)
"I know no places. That is I cannot believe in places. To believe in places is to know hope and to know the emotion of hope is to know beauty. It links us across a horizon and connects us to the world. I find there are no places only my funnyhouse." —A. Kennedy, Funnyhouse of a Negro Repulsed by her black heritage and rejected by white society, Negro Sarah, the mixedblood protagonist in Adrienne Kennedy’s one-act play Funnyhouse o f a Negro (1964) constructs a place of refuge, afunnyhouse for herself. She populates it with four historical figures who represent the warring selves of her mixed ancestry. Rather than empowering her, the iconic figures, namely the Congolese liberator Patrice Lumumba, a hunchback Jesus Christ, Queen Victoria, and the romantic Duchess of Hapsburg entrap her as she is unable to situate her selves in geographical locations: “I try to create a space for myselves in cities, New York, the Midwest, a southern town, but it becomes a lie” (563). Pushed into (non)existence, to a “borderland,” a no man’s land, Sarah is forced to create an alternative place for her selves: “the rooms are my rooms; a Hapsburg chamber, a chamber in a Victorian castle, the hotel where I killed my father, the jungle. These are the places myself exists” (563). The denial of the physical space entails the failure of spiritual reconciliation with the differing selves, so Sarah cannot escape her destiny and commits suicide.